Contraintes et libertés textuelles - Bronckart, Jean-Paul (Caplletra. Revista Internacional de Filologia, 2006)
The article starts from a conception of language according to which the semiotic units that speakers use do not emanate from individual mental processes but from the socialization of representation instruments which, being individual elements initially, have later been involved in processes of communicative circulation. In the same way that, in each language, verbal uses are limited by a series of restrictions in the constitution of some phonic, lexical or morphosyntactic structures, there are also some other constraints that affect textual genres. This means that these are the product of the history of the uses of language and that they work at a praxeologic level. These ideas apply to the study of expression of temporality in the story (récit) and in the narration (narration), with exemplification taken from real texts, mostly of literary character. Both in ordinary verbal work and in literary work, the freedom of the style works on some pre-existent textual models which have to be known and mastered in order to adapt them to the specific conditions of each ordinary verbal action or literary production.